Semi‐field evaluation of the effects of sub‐lethal doses of pesticides, with and without adult Schistocerca gregaria pheromone, on hoppers. Issue 1 (27th June 2016) - Bashir, Magzoub; Hassanali, Ahmed; Korena, Haydar; Bashir, Abdelrahim Widaatalla
Abstract: Previously, we reported a chain of effects induced by phenylacetonitrile, the gregarious‐phase adult cohesion pheromone of the desert locust, Schistocerca gregaria (Forskål) (Orthoptera: Acrididae), on conspecific hoppers. Specifically, the nymphs became hyperactive and displayed high levels of intraspecific predation, as surviving individuals gradually shifted to the solitary phase. The findings suggested that the pheromone could induce a significant level of mortality of the nymphs and predispose them to greater sensitivity to lower doses of insecticides. In this study, we compared the effects of the pheromone and various doses of three pesticides (fipronil, malathion, and carbosulfan) to pheromone‐exposed and unexposed crowd‐reared hoppers in semi‐field enclosures. The pheromone on its own displayed a high level of cumulative mortality of the nymphs (89%). Although combinations with fractional pesticide doses gave control efficiencies that were, in most cases, higher than with individual pesticides, pheromonal and pesticidal effects were only partially complementary, probably because of the feeding‐deterrent effects of the pesticides and the resulting reduction in cannibalism. However, our results demonstrate the possibility of significantly reducing the levels of pesticides used in hopper control and, thus, their negative environmental effects.